Myxomatous mitral valve disease in a miniature poodle - Renita Cynthia Lahagu; Tika Lina Putri; Ronald Tarigan (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2026)
A 3.54 kg female Miniature Poodle presented with persistent daily cough. Examination revealed a cardiac murmur on auscultation, and blood pressure indicated systemic hypertensiaon at 170/120 mmHg. Thoracic radiography demonstrated cardiomegaly with pulmonary edema, suggesting cardiogenic respiratory compromise. Color-flow Doppler echocardiography showed thickened, irregular mitral valve and endocardial surface, left atrial enlargement, and mitral regurgitation, consistent with valvular insufficiency. Based on clinical signs, radiographic findings, and echocardiographic abnormalities, the dog was diagnosed with stage C myxomatous mitral valve disease. Bronchitis and dilated cardiomyopathy were considered differential diagnoses. Prognosis was dubius-infausta because of congestive changes and advanced valvular dysfunction. Treatment consisted of pimobendan, enalapril, furosemide, and potassium L-aspartate supplementation.